2016
DOI: 10.1017/jns.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled, crossover study of the effect of diet on angiopoietin-like protein 4 (ANGPTL4) through modification of the gut microbiome

Abstract: Angiopoietin-like protein 4 (ANGPTL4) is a lipoprotein lipase inhibitor that is involved in lipid metabolism and angiogenesis. Animal studies have suggested that the ANGPTL4 protein is modulated by the gut microbiota, possibly through increased concentrations of SCFA, such as C4, found in whole-fat milk or as a result of fermentation of inulin. This study investigated whether a standardised diet either high in fat content or supplemented with inulin powder would increase plasma ANGPTL4 in overweight men and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In humans, few studies have investigated Angptl4 modulation by GM through SCFA or other metabolites. One study failed to illustrate associations between changes in the microbiota and Angptl4, did not find an influence of changes in diet on Angptl4 concentrations, and did not find a correlation between Angptl4 and plasma lipid levels [ 96 ]. However, this study investigated 18 participants, and larger studies evaluating the effect of GM or its metabolites including SCFAs on Angptl4 are therefore likely of added value.…”
Section: Gut-microbiota-derived Metabolites In Dyslipidemia and Obesitymentioning
confidence: 99%
“…In humans, few studies have investigated Angptl4 modulation by GM through SCFA or other metabolites. One study failed to illustrate associations between changes in the microbiota and Angptl4, did not find an influence of changes in diet on Angptl4 concentrations, and did not find a correlation between Angptl4 and plasma lipid levels [ 96 ]. However, this study investigated 18 participants, and larger studies evaluating the effect of GM or its metabolites including SCFAs on Angptl4 are therefore likely of added value.…”
Section: Gut-microbiota-derived Metabolites In Dyslipidemia and Obesitymentioning
confidence: 99%
“…Recent research also demonstrated that ANGPTL4 promotes bile acid (BA) absorption via the gut microbiota mechanism [ 59 ]. Later, Larsen and co-workers [ 60 ] pointed out that ANGPTL4 can not be effectively regulated by modifying the gut microbiota composition. Furthermore, E40K nucleotide polymorphisms of the ANGPTL4 gene decreased oligomer formation, which is correlated with decreased LPL inhibition activity and significantly lower triglyceride levels [ 17 ].…”
Section: Functions Of Angptl4mentioning
confidence: 99%
“…ANGPTL4 is a lipoprotein lipase inhibitor involved in both lipid metabolism and angiogenesis [27]. It is secreted by entero-endocrine cells and has been proposed as a mediator between gut microbiota and fat storage in adipose tissue [28], by inhibiting the circulating lipoprotein lipase that regulates the uptake of triglycerides in adipocytes [29].…”
Section: Discussionmentioning
confidence: 99%